Analysis of 46.9-nm Pulsed Laser Radiation Aftereffects in Sc/Si Multilayer X-Ray Mirrors - Pershyn, Yuriy P.; Voronov, D. L.; Zubarev, Evgeniy N.; Sevryukova, V. A.; Kondratenko, V. V.; Vaschenko, G.; Grisham, M.; Menoni, C. S.; Rocca, J. J.; Vinogradov, A. V.; Artyukov, I. A.; Uspenskii, Yu. A. (Springer, 2007)
Specific structural changes in Sc/Si multilayers (MLs) irradiated by nanosecond 46.9-nm single laser pulses with fluences of 0.04-5.00 J/cm2 were studied by methods of SEM and cross-sectional TEM. The threshold damage was found to be 0.08 J/cm2 The ML melts down under the fluence F >0.08 J/cm2 and the exothermic reaction of silicide formation starts. Main degradation mechanisms of MLs are discussed. The results of this study can be used for development of advanced multilayer mirrors capable handling the intense radiation conditions of new generation coherent X-ray sources.

Специфічні структурні зміни в багатошарах (МШ) Sc/Si, опромінених наносекундними одиночними лазерними імпульсами 46,9 нм з флюенсом 0,04-5,00 Дж/см2, досліджено методами СЕМ та поперечної ТЕМ. Встановлено, що порогове пошкодження становить 0,08 Дж/см2. ML плавиться під впливом потоку F >0,08 Дж/см2, і починається екзотермічна реакція утворення силіциду. Обговорюються основні механізми деградації ML. Результати цього дослідження можуть бути використані для розробки передових багатошарових дзеркал, здатних працювати в умовах інтенсивного випромінювання когерентних джерел рентгенівського випромінювання нового покоління.
Keywords: laser radiation; specific structural changes; single laser pulses; methods of SEM; наносекундні одиночні лазерні імпульси; cпецифічні структурні зміни; імпульсне лазерне випромінювання; екзотермічна реакція утворення силіциду